FAIM Opposes Aggregation of Mutant SOD1 That Typifies Some Forms of Familial Amyotrophic Lateral Sclerosis - Kaku, Hiroaki; Ludlow, Alexander V.; Gutknecht, Michael F.; Rothstein, Thomas L. (Frontiers in Neuroscience, 2020)
Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative illness that is unremittingly fatal and for which no effective treatment exists. All forms of ALS are characterized by protein aggregation. In familial forms of ALS, specific and heritable aggregation-prone proteins have been identified, such as mutant superoxide dismutase (SOD1). It has been suggested that a factor capable of preventing mutant SOD1 protein aggregation and/or disassembling mutant SOD1 protein aggregates would ameliorate SOD1-associated forms of familial ALS. Here we identify FAIM, a highly evolutionarily conserved 20 kDa protein, as an agent with this activity. We show FAIM counteracts intracellular accumulation of mutant SOD1 protein aggregates, which is increased in the absence of FAIM, as determined by pulse-shape analysis and filter trap assays. In a cell-free system, FAIM inhibits aggregation of mutant SOD1, and further disassembles and solubilizes established mutant SOD1 protein aggregates, as determined by thioflavin T, filter trap, and sedimentation assays. In sum, we report here a previously unknown activity of FAIM that opposes ALS disease-related protein aggregation and promotes proteostasis of an aggregation-prone ALS protein.